Perkembangan Sistem Model Pembelajaran Daring di Universitas Alkhairaat - Dedi Siswanto (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The development of information and communication technology has significantly transformed learning systems in higher education, including at Alkhairaat University. This study aims to analyze the online learning system implemented at Alkhairaat University, examine the development of online learning methods, identify the supporting and inhibiting factors, and evaluate the effectiveness of its implementation. This study employed a descriptive qualitative research method. Primary data were collected through interviews with lecturers and students, while secondary data were obtained from institutional documents. The collected data were analyzed qualitatively through data reduction, data presentation, and conclusion drawing. The findings indicate that the online learning system at Alkhairaat University utilizes a Moodle-based Learning Management System (LMS) supported by Zoom, Google Meet, and WhatsApp as learning communication platforms. The development of online learning has progressed through three stages: the emergency learning stage in 2020, the adaptation stage through the optimization of the LMS during 2021–2022, and the development stage toward a blended learning model beginning in 2023. Supporting factors include the availability of the LMS, internet data assistance, and access to digital devices among lecturers and students. Meanwhile, the major challenges include unstable internet connectivity, limited digital literacy among some users, and reduced face-to-face interaction during the learning process. Overall, online learning has proven effective in increasing learning flexibility, expanding access to learning resources, and promoting students' independent learning. However, it remains less effective for courses requiring direct practical activities. Therefore, the implementation of a blended learning model is considered an appropriate strategy for improving the quality of teaching and learning at Alkhairaat University.